Cameroon : Fourth Review under the Extended Credit Facility Arrangement and Requests for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Cameroon. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Cameroon's Fourth Review Under the Extended Credit Facility Arrangement and Requests for Waivers of Nonobservance of Performance Criteria and Modification of Performance Criteria. Growth is estimated to have rebounded to 4 percent in 2018, supported by stronger-than-anticipated oil and gas production and Africa Cup of Nations projects. Program implementation has improved from a year ago, however, challenges remain. Refraining from new nonconcessional borrowing and strictly adhering to the disbursement plan for contracted-but-undisbursed loans are essential to preserving debt sustainability. Further project prioritization and enhanced investment efficiency will help address developmental needs while supporting prudent debt management. Cameroon's program continues to be supported by the implementation of supportive policies and reforms by the regional institutions in the areas of foreign exchange regulations and monetary policy framework and to support an increase in regional net foreign assets, which are critical to the program's success.